The dynamics of the nutrients in degraded Vertic Endoaquepts of rainfed rice fields with soil ameliorant and soil tillage management - Nourma Al Viandari; Anicetus Wihardjaka; Heru Bagus Pulunggono; Suwardi Suwardi; Mas Teddy Sutriadi (Journal of Degraded and Mining Lands Management, 2023)
Intensive land use in the long term can cause land degradation, affecting soil fertility, especially on Vertic Endoaquepts in Pati that have been managed as rainfed rice fields. The characteristics of rainfed rice fields are low nutrient availability and rice yields. This study aimed to determine the effect of tillage depth management and soil ameliorants on nutrient availability, plant uptake, and rice yield in rainfed rice fields. The field experiment that was conducted at farmer’s field used a split-plot design. The main plot was the treatment of tillage depth treatments (OT), with depths of 10 cm (T1) and 20 cm (T2). The subplots were ameliorant treatments (A), consisting of A1 = sugarcane leaf compost, A2 = rice straw compost, A3 = chicken manure, and A4 = cow manure, with each dose of 5 t ha-1. The Inpari 32 rice variety was grown for 95 days. Available N, P and K of the soil were measured at 0, 62, and 94 days after transplanting (DAT). Plant N, P, and K contents, plant height, number of tillers, and rice yield were measured at 62 DAT. The results showed that the interaction of soil depth and ameliorant significantly affected soil available P and K but had no significant effect on soil available N. Ameliorant treatment of cow manure significantly increased rice yield.